Determinantes da variabilidade da frequência cardíaca nos pacientes com Doença Pulmonar Obstrutiva crônica - Santana, Mylena Maria Salgueiro (2015)
Present study had examined the influence of the sympathetic modulation of the hypoxic respiratory pattern in patients with chronic obstructive pulmonary disease (COPD). 12 were evaluated with the disease and, for comparative purposes, 10 healthy patients also participated. The subjects were assessed for Heart Rate Variability (HRV) through Finapress, and concurrently monitored oxygen saturation and respiratory rate, for 5 minutes at rest. After this evaluation, spirometry was performed on each patient, resulting in the forced expiratory volume values in one second (FEV1) and the FEV1 and the Forced Vital Capacity (FVC). When correlated the levels of Oxygen Saturation (SpO2) and Tiffeneau index, there is direct variation between spirometric index and SpO2 (ρ = 0.45). The reverse occurs between systolic blood pressure (SBP) and SpO2 and FEV1 and band Lf SAP (ρ = -0.65). When analyzed HRV in the time domain, a statistically significant difference between groups for the band Lf (p = 0.01) and LF / HF ratio (p = 0.02). It was seen that, when compared to healthy subjects, patients with COPD had lower values of HRV increased SBP and decrease in oxygen saturation (SpO2) and spirometric indices. Still, the drop in autonomic function seems to be more impaired in patients where FEV1 indexes and the FEV1 / FVC are lower. Apparently, the drop in SpO2, due to the loss in gas exchange, seems to increase the sympathetic modulation, increasing the SBP levels.